PET-CT and PET-MRI in Oncology A Practical Guide - Peller, Patrick; Subramaniam, Rathan; Guermazi, Ali.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Over the past decade, PET-CT has achieved great success owing to its ability to simultaneously image structure and function, and show how the two are related. As a consequence, it has increasingly replaced stand-alone PET for most oncologic indications. More recently, PET-MRI has also been developed, and it represents an exciting novel option that promises to have applications in oncology as well as neurology. The first part of this book discusses the basics of these dual-modality techniques, including the scanners, radiotracers, scan performance, quantitation, and scan interpretation. As a result, the reader will learn how to perform the techniques to maximum benefit. The second part of the book then presents in detail the PET-CT and PET-MRI findings in cancers of the different body systems. Applications in pediatric patients, assessment of therapy response, and patients with metastatic disease are discussed separately. The final two chapters address the use of PET/CT in radiotherapy planning and examine areas of controversy. The authors are world-renowned experts from North America, Europe, and Australia, and the lucid text is complemented by numerous high-quality illustrations.
Part 1 - Basics: 1 PET/CT and PET/MRI Scanners -- 2 PET Radiochemistry and Radiopharmacy -- 3 Practical PET/CT Operation -- 4 PET/CT Quantitation -- 5 PET/CT Interpretation -- Part 2 - Oncologic applications: 6 Central Nervous System -- 7 Head and Neck -- 8 Chest -- 9 Breast -- 10 Gastro-Intestinal -- 11 Genito-Urinary -- 12 Musculoskeletal and Soft Tissue Sarcoma -- 13 Hematologic -- 14 Dermatologic -- 15. Pediatric -- 16 Assessing Therapy -- 17 Metastatic Disease -- 18 Radiotherapy Planning -- 19 PET/CT Controversies.
Keywords: Medicine; Radiology, Medical; Nuclear medicine; Oncology; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Nuclear Medicine; Oncology